(untitled) (Journal of Hama University, 2021)
The study was conducted to study the effect of the type of fertilizer and the size of the bulbs grown on the growth and flowering of the Lilium longiflorum under the conditions of the city of Hama. The experiment was designed according to the dissimilar sectors, the main factor is the quality of the fertilizer (5) (sheepskin manuare, poultry manure, Metallic balanced, Metallic high phosphorus, (Without fertilization), and The splitting factor is the size of the bulbs and the number is / 2 / two large bulbs perimeter (21-25 cm), and small bulbs have circumference (17-20 cm).The following shows: 1- - The plants responded فخ the soil and fertilization, as the balanced mineral fertilization treatment exceeded the rest of the fertilization treatments in the plant and soil nitrogen content, and the high-phosphorous mineral fertilization treatment surpassed the rest of the fertilization treatments in the phosphorus content of the plant and soil, and as for potash, it surpassed organic fertilizers (sheepskin manuare. poultry manure, on mineral fertilization treatments in soil and plant potash content) 2- The treatment of using large bulbs (21-25 cm) was significantly more than the treatment of using small bulbs (17-20 cm) in the content of the plant sample of (nitrogen, phosphorus and potash%), while the treatment of using small bulbs outwardly exceeded the soil content of (Nitrogen, phosphorous and potash mg / kg) on ​​the treatment of large-sized bulbs.